Political brand identity: An examination of the complexities of Conservative brand and internal market engagement during the 2010 UK General Election campaign. Issue 1 (2nd January 2016) - Pich, Christopher; Dean, Dianne; Punjaisri, Khanyapuss
Abstract : This paper seeks to build an understanding of the importance of internal communications when building a strong political brand. Using Kapferer's brand prism as a conceptual framework, the paper explores UK Conservative Party members' attitudes towards the development of the Conservative brand as personified by David Cameron. There are clear implications for political strategists as the findings suggest that it is crucial to engage the internal market in the co-creation of the marketing communications strategy for as brand evangelists they interpret the brand promise at the local level.